Treatment of the spent caustic wastewater using g-C3N4/CeFeO3 nanocomposites in a Taylor–Couette photocatalytic reactor - Soleiman Mosleh; Mostafa Narimani; Atousa Daneshyar (Advances in Environmental Technology, 2025)
The discharge of spent caustic wastewater (SCW) from petrochemical plants poses a significant environmental concern due to its high Chemical Oxygen Demand (COD). This research investigates the efficacy of a photocatalytic degradation process for treating SCW. The primary objective is to achieve maximum COD reduction while carefully managing the hydrogen peroxide (H2O2) to SCW ratio and optimizing key operational parameters. To this end, g-C3N4/CeFeO3 nanocomposites were synthesized as efficient photocatalysts and thoroughly characterized using XRD, FE-SEM, EDX, FT-IR, DRS, and BET techniques. Under optimized conditions—specifically a photocatalyst loading of 1.0 g/L, an H2O2/SCW ratio of 2.50 mL/L, a pH of 5.0, a reaction time of 60 minutes, and an aeration rate of 1.50 L/min—a remarkable 98% COD removal was achieved. Furthermore, catalyst recycling studies demonstrated the reusability of the g-C3N4/CeFeO3 nanocomposites for at least four consecutive treatment cycles, indicating their potential for sustainable application. Recognizing the limitations of conventional reactors for scaling up photocatalytic processes, this study also proposes the integration of the developed photocatalyst with advanced reactor designs, such as Taylor-Couette reactors, to enhance mass and photon transfer. This integration represents a critical future direction for achieving industrially viable wastewater treatment solutions.